2012
DOI: 10.1128/jvi.00895-12
|View full text |Cite
|
Sign up to set email alerts
|

Latent HIV-1 Infection Occurs in Multiple Subsets of Hematopoietic Progenitor Cells and Is Reversed by NF-κB Activation

Abstract: The ability of HIV-1 to establish a latent infection presents a barrier to curing HIV. The best-studied reservoir of latent virus in vivo is resting memory CD4 + T cells, but it has recently been shown that CD34 + hematopoietic progenitor cells (HPCs) can also become latently infected by HIV-1 in vitro and in vivo . CD34 + cells are not homogenous, however, and it is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 86 publications
(99 reference statements)
3
66
0
1
Order By: Relevance
“…Indeed, other activators that work via the NF-B system and activators that employ other mechanisms, such as activators that act epigenetically, activate HIV in some model systems, but not in others (22,73). Some activators can even exhibit antagonistic effects for HIV activation in some systems and additive or synergistic effects in others (22).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, other activators that work via the NF-B system and activators that employ other mechanisms, such as activators that act epigenetically, activate HIV in some model systems, but not in others (22,73). Some activators can even exhibit antagonistic effects for HIV activation in some systems and additive or synergistic effects in others (22).…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been shown that some populations of progenitors can become infected with reporter viruses in vitro, 38 this has not been demonstrated with wild-type HIV nor in an animal model system. Recent work by others shows that HIV-1 DNA could not be detected in highly purified bone marrow CD341 cells derived from patients.…”
Section: Org Frommentioning
confidence: 99%
“…9,10 It remains unclear whether HCMV latent infection would affect the expression of HIV-1 restriction factors in CD34 1 cells. Therefore, to examine this, SAMHD1, APOBEC3G, Mx2, and tetherin gene expression was determined by qPCR in a time course experiment in PB-CD34 cells.…”
Section: Hiv-1 Restriction Factors Are Downregulated By Hcmv Latent Imentioning
confidence: 99%
“…9,10 Latent HIV-1 exists in the proviral state in multiple hematopoietic progenitor cell subsets that is regulated by NF-kB activation. 10 As with other myeloid-lineage cells, however, CD34…”
Section: Recent Studies Showed That Infection Of Cd34mentioning
confidence: 99%
See 1 more Smart Citation